Ion fluxes and electro-osmotic fluid flow in electrolytes around a metallic nanowire tip under large applied ac voltage - Poetschke, Markus; Bobeth, Manfred; Cuniberti, Gianaurelio (Langmuir, 2013)
Motivated by the analysis of electrochemical growth of metallic nanowires from solution, we studied ion fluxes near nanoelectrodes in a binary symmetric electrolyte on the basis of the modified Poisson-Nernst-Planck equations in the strongly nonlinear region at large applied ac voltage. For an approximate calculation of the electric field near the nanowire tip, concentric spherical blocking electrodes were considered with radius of the inner electrode being of typically a few ten nanometers. The spatiotemporal evolution of the ion concentrations within this spherical model was calculated numerically by using the finite element method. The potential drop at the electric double layer, the electric field enhancement at the electrode surface, and the field screening in the bulk solution were determined for different bulk concentrations, ac voltages, and frequencies. The appearance of ac electro-osmotic fluid flow at the tip of a growing metallic nanowire is discussed, based on an estimation of the body force in the liquid near the nanowire tip, which was modeled by a cylinder with hemispherical cap. Electric field components tangential to the electrode surface exist near the contact between cylinder and hemisphere. Our analysis suggests that ac electro-osmotic flow causes an additional convective transport of metal complexes to the tip of the growing metal nanowire and thus affects the nanowire growth velocity. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20